On the absorbability of herd behaviour and informational cascades: an experimental analysis - Andrea Morone; Annamaria Fiore; Serena Sandri (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2007)
A theory is said to be fully absorbable whenever its own acceptance by all of the individuals belonging to a certain population does not question its predictive validity. This accounts for strategic equilibria and can be related to the logic underlying convergence of behaviour and intentional herding in sequential games. This paper discusses the absorbability of informational cascades' theory by bounded rational decision-makers and analyses whether providing individuals with theoretic information on informational cascades affects overall probability of herding phenomena to occur as well as whether an incorrect cascade can be reversed because of bounded rational adapting of the theory's prescriptive.
Keywords: D8; C91; C72; 330; Theory absorption; Herd behaviour; Informational cascades; Herdenverhalten; Informationsverhalten; Beschränkte Rationalität; Experiment; theory absorption